Pengaruh Modal Usaha dan Motivasi terhadap Minat Berwirausaha pada Mahasiswa - Novi Mubyarto; Rina Juniati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
A strong entrepreneurial sector plays a crucial role in a country's economic growth. Entrepreneurship not only contributes to creating jobs, but also increases productivity and encourages innovation. Therefore, it is very strategic to foster interest in entrepreneurship, especially among students and the younger generation. There are several factors that influence interest in entrepreneurship among students, one of these factors is business capital and motivation. The aim of this research is to find out whether there is an influence of business capital and motivation on interest in entrepreneurship among students of the Sharia Economics Study Program at Island Sulthan Thaha Saifuddin University, Jambi. The method used in this research is a quantitative method. The research sample consisted of 96 students using a sampling technique, namely Purposive Sampling. The results of this research show that both variables have a positive and significant effect on interest in entrepreneurship among students in the sharia economics study program. Simultaneously, the business capital and motivation variables have a significant influence on the entrepreneurial interest variable. The R Square value is 0.561 or 56.1%, which means that 56.1% of changes in the dependent variable can be explained by the independent variable, while the remaining 43.9% is influenced by other variables not included in this research. The Adjusted R Square value = 0.551 shows that after adjustment, this model still has good abilities in explaining the dependent variable. Apart from that, the R value = 0.749 shows a strong relationship between the independent variable and the dependent variable. The Islamic economic view of entrepreneurship is one of the noble recommendations for humans in working.